2016
DOI: 10.1016/j.ijgo.2016.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pre‐eclampsia and assessment of severity through examination of the placenta with acoustic radiation force impulse elastography

Abstract: Measurement of the placental SWV with ARFI imaging is a useful additional method for the diagnosis of pre-eclampsia and for determination of the disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…This is a credible hypothesis already suggested by studies ( Table 5 ). Among this literature, several ex vivo studies [ 20 , 26 , 36 ] and in vivo studies [ 19 , 22 , 27 , 32 35 ] compared normal and insufficient placentas in humans (either preeclampsia, IUGR or both).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a credible hypothesis already suggested by studies ( Table 5 ). Among this literature, several ex vivo studies [ 20 , 26 , 36 ] and in vivo studies [ 19 , 22 , 27 , 32 35 ] compared normal and insufficient placentas in humans (either preeclampsia, IUGR or both).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they have employed a diverse range of elastography techniques: strain elastography [ 19 , 26 , 30 ], ARFI [ 20 , 28 , 32 34 ], or SWE [ 21 , 22 , 25 , 27 , 29 ]. The orders of magnitude of the measurements sometimes differed from one study to another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding placentomes, it is known that although individual placentomes may continue to undergo morphologic transformations as gestation advances, major placental growth is complete by mid-gestation in sheep (Liu et al, 2018;Reynolds et al, 2005) justifying the constant SWV observed. Elastographic evaluation of placenta was validated by previous studies (Alan, Tunç, Agacayak, & Bilici, 2016;Rumball, Harding, Oliver, & Bloomfield, 2008;Yuksel et al, 2016), which detected lower and higher placental stiffness in women with pre-eclampsia and gestational diabetes mellitus, respectively. It allows the obstetrician-gynaecologist to perform not only an early diagnosis, but also a rapid and successful intervention to save the lives of mother and foetus.…”
Section: Variablesmentioning
confidence: 92%
“…Recent work has shown that the placenta and umbilical cord undergo biomechanical changes during disease, which could potentially be used as an evaluation parameter for disease detection. For example, the in vivo evaluation of the placenta stiffness via ultrasound elastography was suggested as a means to detect PE (Cimsit et al, 2015a , b ; Kiliç et al, 2015 ; Alan et al, 2016b ; Erbil et al, 2016 ) and IUGR (Quibel et al, 2015 ; Durhan et al, 2017 ; Habibi et al, 2017 ). Further, biofluid mechanics analysis of the placenta and evaluation of the umbilical-placenta vascular mechanical properties will improve our understanding about the placenta biotransport phenomenon and its vascular growth and remodeling process, respectively.…”
Section: Introductionmentioning
confidence: 99%